Synthetic Biology Open Language Visual (SBOL Visual) Version 2.0 - Cox,R; Madsen,C; McLaughlin,J; Nguyen,T; Roehner,N; Bartley,B; Bhatia,S; Bissell,M; Clancy,K; Gorochowski,T; Grunberg,R; Luna,A; et al. (Journal of Integrative Bioinformatics, 2018)
People who are engineering biological organisms often find it useful to communicate in diagrams, both about the structure of the nucleic acid sequences that they are engineering and about the functional relationships between sequence features and other molecular species. Some typical practices and conventions have begun to emerge for such diagrams. The Synthetic Biology Open Language Visual (SBOL Visual) has been developed as a standard for organizing and systematizing such conventions in order to produce a coherent language for expressing the structure and function of genetic designs. This document details version 2.0 of SBOL Visual, which builds on the prior SBOL Visual 1.0 standard by expanding diagram syntax to include functional interactions and molecular species, making the relationship between diagrams and the SBOL data model explicit, supporting families of symbol variants, clarifying a number of requirements and best practices, and significantly expanding the collection of diagram glyphs.